2016
DOI: 10.1007/s12665-015-5158-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and evaluation of landscape ecological status using geographic indices extracted from remote sensing imagery of the Pearl River Delta, China, between 1998 and 2008

Abstract: This paper presents a method of mapping and monitoring ecological quality and environmental change using an ecological evaluation model (EEM), which is based on remote sensing data of the Pearl River Delta region in Guangdong, China. Five geographical indices were selected: Impervious Surface, Normalized Difference Vegetation Index, Land Surface Temperature, and Greenness and Brightness generated from the Tasseled Cap Transformation. These geographical indices are of ecological significance and they were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Among these indices, the normalized difference vegetation index (NDVI) and land surface temperature (LST) are the most common [21][22][23][24]. Because single satellite-based parameters, which are often used, show only one aspect of the ecological situation, they are not sufficient to reflect the extent and spatiotemporal characteristics of ecological quality change comprehensively [25][26][27]. Some studies have shown that a combination of several satellite-based indices can model spatiotemporal changes in surface ecological conditions more accurately [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these indices, the normalized difference vegetation index (NDVI) and land surface temperature (LST) are the most common [21][22][23][24]. Because single satellite-based parameters, which are often used, show only one aspect of the ecological situation, they are not sufficient to reflect the extent and spatiotemporal characteristics of ecological quality change comprehensively [25][26][27]. Some studies have shown that a combination of several satellite-based indices can model spatiotemporal changes in surface ecological conditions more accurately [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Because single satellite-based parameters, which are often used, show only one aspect of the ecological situation, they are not sufficient to reflect the extent and spatiotemporal characteristics of ecological quality change comprehensively [25][26][27]. Some studies have shown that a combination of several satellite-based indices can model spatiotemporal changes in surface ecological conditions more accurately [27][28][29]. Surface ecological conditions are one of the key factors in the improvement of ecosystem structure and performance and the maintenance of ecosystem characteristics and services [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, global warming, air pollution, forest and grassland degradation, the irresponsible use of water resources, and the sustainable use of natural resources in all areas have been brought to the agenda [4][5][6][7]. Ecologists have improved their understanding of ecosystem processes, including landscape dynamics, energy and material circulation of species and the driving mechanism from different spatial scales [8][9]. In coal mining areas, a special and complex type of geographic area, long-term, large-scale and intense mining inevitably damage the primary geology of coal deposits, occupy and even destroy large amounts of land and cause vegetation degradation, soil erosion by water, a decline in biodiversity and other serious ecological problems [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative landscape information over time is considered the first necessity for understanding consequences from landscape changes [21]. In recent years, various means such as remote sensing (RS) and geographic information system (GIS), as well as a large number of indices representing the geometric features of landscape, have been widely used in the study of landscape pattern changes [8,[22][23][24]. LPC in coal mining areas are a comprehensive reflection of the impact of mining activities on local ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Warntz advocated that ecological security patterns could be constructed by reference to ecological resistance surfaces [26], and Yu applied the concept of ESP to the construction of greenways, biodiversity conservation and urban planning [17]. Based on comprehensive discussions of landscape ecology and land use [27], multiple models and methodologies have been used to explore deeper connections between ecology and land use, and specific research on individual regions and objectives has been widely discussed [28][29][30][31][32]. Studies on land planning and management have mainly been concerned with ecological security evaluation by establishing an analytical framework and evaluation models such as the multi-objective optimization model, the cellular automata model and the calculation of ecosystem services value [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%